2005
DOI: 10.1152/ajpheart.01040.2004
|View full text |Cite
|
Sign up to set email alerts
|

Arterial baroreflex alters strength and mechanisms of muscle metaboreflex during dynamic exercise

Abstract: . Arterial baroreflex alters strength and mechanisms of muscle metaboreflex during dynamic exercise. Am J Physiol Heart Circ Physiol 288: H1374 -H1380, 2005. First published November 11, 2004; doi:10.1152/ajpheart.01040. 2004.-Previous studies showed that the arterial baroreflex opposes the pressor response mediated by muscle metaboreflex activation during mild dynamic exercise. However, no studies have investigated the mechanisms contributing to metaboreflex-mediated pressor responses during dynamic exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
88
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 38 publications
(76 reference statements)
8
88
1
Order By: Relevance
“…The role of baroreflex in attenuating the circulatory response to exercise has been recently described [35].…”
Section: Discussionmentioning
confidence: 99%
“…The role of baroreflex in attenuating the circulatory response to exercise has been recently described [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that the arterial baroreflex buffers the muscle metaboreflex-mediated pressor response (30,55). Nishiyasu et al (44) showed that cardiac parasympathetic tone increases during PEMI in humans and suggested that this increase may form part of a counteraction by the arterial baroreflex in response to the rise in blood pressure induced by the muscle metaboreflex.…”
mentioning
confidence: 99%
“…Although differences in the type of exercise and muscle mass used in the exercise could potentially affect the results, an alternative explanation for this inconsistency is that the components of the muscle metaboreflex-mediated pressor response vary widely among human subjects. Previous studies (25,26,30,67) have shown that activation of the muscle metaboreflex during submaximal treadmill exercise in dogs with reduced hindlimb blood flow elicits a pressor response mediated primarily by an increase in CO. However, the mechanism of the pressor response shifts to increased peripheral vasoconstriction when the ability to increase CO is limited, such as in heart failure or during maximal exercise (2,20).…”
mentioning
confidence: 99%
“…After sinoarterial baroreceptor denervation, the metaboreflex pressor response increases twofold (49,102). In this setting, substantial peripheral vasoconstriction now accompanies the rise in cardiac output (50). Thus the arterial baroreflex buffers the muscle metaboreflex mainly by preventing peripheral vasoconstriction.…”
Section: Impaired Baroreflex Buffering Of Muscle Metaboreflex In Hearmentioning
confidence: 99%